Propuesta pedagógica basada en el enfoque learner centered para el desarrollo de la habilidad de speaking - Palacios García, Jonathan Ricardo (Machala : Universidad Técnica de Machala, 2021)
This research project demonstrates outcomes of the development of concatenated teaching activities focused on influencing the improvement of communication skills oriented to the Speaking skill, it was obtained in students of the seventh grade of General Secondary Education of the School "Manuel Isaac Encalada Zúñiga" at Buenavista parish in Pasaje, after the bibliographic review of the exposed variables, it is sustained that when putting into practice the “learner-centered” approach in oral communication activities, these develop favorably. The present research work was designed according to qualitative parameters, of an action-research type endorsed by the socio-critical paradigm. The techniques used for data collection and processing were observation, semi-structured interview, and content analysis. The teaching intervention proposal is aimed at establishing pedagogical reference points in which the teacher can take advantage of the characteristics and particularities of the students to develop Speaking skills. Finally, it seeks to encourage teachers and future teachers to take advantage of the above according to the focus centered on student learning for the benefit of the cognitive, social, and cultural development of students.
El presente proyecto investigativo demuestra el resultado del desarrollo de actividades docentes concatenadas y enfocadas a incidir en la mejora de las habilidades comunicativas orientadas a la habilidad de Speaking obtenidas en los estudiantes del séptimo grado de Educación General Media de la Escuela “Manuel Isaac Encalada Zúñiga” de la parroquia Buenavista en el cantón Pasaje, luego de la revisión bibliográfica de las variables expuestas se sustenta que al poner en práctica el enfoque “learner-centered” en las actividades comunicativas orales estas se desarrollan favorablemente. El presente trabajo investigativo fue diseñado acorde a parámetros de carácter cualitativo, de tipo investigación-acción avalado por el paradigma socio crítico. Las técnicas utilizadas para la recolección y procesamiento de datos fueron la observación, la entrevista semiestructrada y análisis de contenido. La propuesta de intervención docente está orientada a establecer puntos de referencia pedagógicos en los que el docente pueda aprovechar las características y particularidades de los estudiantes para desarrollar la habilidad de Speaking. Finalmente, se busca incentivar a los maestros y futuros docentes a tomar ventaja de lo expuesto acorde al enfoque centrado en el aprendizaje del estudiante en beneficio del desarrollo cognoscitivo, social y cultural de los estudiantes.
Keywords: LEARNER; SPEAKING; CENTERED; COMUNICATION